Evaluation of the effects of chronic biomass fuel smoke exposure on peripheral endothelial functions: an observational study - Buturak, Ali; Genc, Ahmet; Ulus, Ozden Sila; Duygu, Egemen; Okmen, Arda Sanli; Uyarel, Huseyin (TURKISH SOC CARDIOLOGY, 2011)
Objective: To evaluate the effect of chronic biomass fuel (BMF) smoke exposure on peripheral endothelial functions. Methods: Forty-seven healthy subjects who have been exposed to BMF smoke since birth (mean age 31.6 +/- 6.8 years, 21 male) were enrolled in the present cross-sectional observational study. The control group consisted of 32 healthy subjects (mean age 27.9 +/- 4.4 years, 11 male). The carotid intima media thickness (CIMT), flow associated dilatation (FAD \%) and endothelium independent vasodilatation (GTN \%) were assessed in all subjects. The carotid CIMT was defined as the distance between the leading edge of the lumen intima and the media adventitia interfaces. FAD \% was defined as the percentage change in the internal diameter of the brachial artery during reactive hyperemia related to the baseline. GTN \% was defined as the change in diameter in response to the application of 400 mu g of glyceril trinitrate relative to the baseline scan at the end of the fourth minute. Statistical analysis was performed using Student's t-test, Chi-square test and Spearman rank order correlation analysis. Results: The average exposure time of the subjects to biomass fuel smoke was 31.7 +/- 6.6 years. They have been exposed to dung inhalation products meanly 8.3 +/- 1.8 months in a year seasonally. The average daily exposure time was 15.7 +/- 3.3 hours. CIMT values of the two groups were not statistically different from each other (0.47 +/- 0.09 vs. 0.49 +/- 0.06 mm, p=0.138). However, a markedly reduced FAD \% was determined in the study group (5.06 +/- 4.95 vs. 10.7 +/- 4.64, p < 0.001). And GTN \% of the BMF exposed group was significantly lower than the control group (14.41 +/- 8.47 vs. 21.85 +/- 7.87, p < 0.001). Conclusion: FAD \% and GTN \% are markedly reduced in the individuals who have been exposed to BMF smoke inhalation products. Therefore, chronic BMF smoke exposure may be a risk factor for the development of endothelial dysfunction. (Anadolu Kardiyol Derg 2011

11:492-7)
Keywords: Biomass fuel smoke exposure; endothelial dysfunction; early atherosclerosis; air pollution; adverse effects